Strategi Bimbingan Guru PAI Dalam Mengatasi Rendahnya Minat Belajar Siswa Dalam Pelajaran SKI Kelas XI Di MA Rohani Ikhwanul Muslimin Desa Penggalangan Kec. Tebing Syahbandar Kab. Serdang Bedagai - Ritonga, Siti Nurzeda; Rambe, Masrina; Siregar, Chairuddin (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This study aims to analyze the guidance strategies employed by Islamic Education (PAI) teachers to address the low learning interest of students in the History of Islamic Culture (SKI) subject for the eleventh grade at MA Rohani Ikhwanul Muslimin, Desa Penggalangan, Tebing Syahbandar District, Serdang Bedagai Regency. The research utilizes a descriptive qualitative method, with data collected through interviews, observations, and document analysis. The findings indicate that the PAI teachers’ guidance strategies include motivational approaches, varied teaching methods, and increased student engagement in learning activities. Motivational approaches involve providing positive reinforcement such as rewards and constructive feedback. Varied teaching methods, including discussions, question-and-answer sessions, and the use of multimedia, are employed to make the subject matter more engaging. Additionally, teachers strive to enhance student involvement through supplementary activities such as seminars and workshops. These strategies are intended to boost students' interest in SKI by creating a more engaging and enjoyable learning environment. The study concludes that effective guidance requires a combination of motivation, diverse methods, and active student participation in the learning process